The root systems of Permian arborescent sphenopsids: Evidence from the Northern and Southern hemispheres - Rössler, Ronny; Merbitz, Mathias; Annacker, Volker; Luthardt, Ludwig; Noll, Robert; Neregato, Rodrigo [UNESP]; Rohn, Rosemarie [UNESP] (My University, 2014)
Anatomically preserved calamitalean trunks are described from the Permian fossil forests of Chemnitz, Germany, and Tocantins, central-north Brazil. Several trunk bases were found in situ, still rooting in their former substrate or in parautochthonous sediments and revealing multiple organic connections between stems and roots. The new evidence of several free-stemmed Permian calamitaleans from different fossil lagerstätten and different taphonomic modes from the Northern and Southern hemispheres has implications for understanding calamite growth and challenges the universal validity of the reconstruction of rhizome-bearing woody trees. Whereas the stems belong to different species of the widely distributed genus Arthropitys GOEPPERT 1864, among them the generitype A. bistriata (Cotta) emend. RÖSSLER, FENG & NOLL 2012 the attached roots represent the largest calamite roots ever found and incorporate a broad spectrum ofpreservational forms and ontogenetic stages. The latter are represented by the root genera Astromyelon WILLIAMSON 1878, Myriophylloides HICK & CASH 1881 and Asthenomyelon LHISTIKOW 1962 that were evidenced for the first time from Chemnitz, the type locality of Arthropitys and Calamitea (COTTA) emend. RÖSSLER & NOLL 2007. Branched, stem-borne, adventitious root systems exhibit similar architectures, arise from different nodes of the lowermost trunks and anchor the trees in different substrates. Developmental features were analysed in first- to third-order roots, which possess clearly-defined concentric tissue zones: epidermis/periderm, cortex, endodermis and central vascular tissue with or without pith. First-order roots, in particular, show considerable secondary growth. Numerous zones of concentric density variation in the secondary xylem indicate some kind of seasonality in the early Permian environments.
Keywords: Anatomy; Calamitaleans; Fossil forest; Petrifaction; Roots